2016
DOI: 10.3402/meo.v21.31196
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Mind Body Medicine course on medical student empathy: a pilot study

Abstract: IntroductionEmpathy among medical practitioners has been shown to affect patient care and outcomes. Factors such as stress and depression are known to have a negative impact on medical student empathy. Approaches such as mindfulness, meditation, and other mind–body techniques can enhance empathy and reverse burnout symptoms. In the present study, we evaluated impact of Mind Body Medicine (MBM) course on perceived stress and empathy on first-year medical students.MethodsThirteen first-year medical students in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…We found no significant effect of our online intervention on empathy levels, although there was an increase in the expected direction. Our results concur with previous studies that found no significant effect of in-person mindfulness training on medical student empathy 17 , 37 , 38 although positive effects have also been reported. 12 , 39 The lack of statistically significant changes in empathy may be attributed, in part, to properties of the JES-S.…”
Section: Discussionsupporting
confidence: 93%
“…We found no significant effect of our online intervention on empathy levels, although there was an increase in the expected direction. Our results concur with previous studies that found no significant effect of in-person mindfulness training on medical student empathy 17 , 37 , 38 although positive effects have also been reported. 12 , 39 The lack of statistically significant changes in empathy may be attributed, in part, to properties of the JES-S.…”
Section: Discussionsupporting
confidence: 93%
“…This ability to appreciate how similar circumstances may affect individuals differently is an essential trait for physicians, who must tailor treatments to achieve the personal goals of each patient. Empathy is also beneficial for the provider, as it corresponds to higher rates of job satisfaction and improved clinical practice [18]. Yet, while the importance of empathy as a core competency for physicians is well recognized, the way in which to promote the development of this skill is relatively unknown [19].…”
Section: Discussionmentioning
confidence: 99%
“…Being empathic is one of the many factors contributing to the enhancement of the patient-physician relationship [18]. In the clinical setting, empathy includes the ability to listen to a patient, understand their perspective, sympathize with their experience, and express understanding, respect, and support.…”
Section: Introductionmentioning
confidence: 99%
“…From the curricular design and adoption of academic experiences that could potentially have a positive impact on empathy formation, several strategies and techniques have been described [34][35][36][37][38]. However, it is not yet clear whether the positive change in the levels of empathy achieved by these specific interventions may last in time.…”
Section: Compassionate Carementioning
confidence: 99%